Pemberdayaan potensi masyarakat berbasis peternakan kambing di Gampong Ajee Rayeuk Kabupaten Aceh Besar (Empowerment of community potential based on goat farm in Ajee Rayeuk Village District of Aceh Besar) - Sayuti, Arman; Panjaitan, Budianto; Syafruddin, S; Roslizawaty, R; Armansyah, T.; Sutriana, Amalia; Aliza, Dwinna; Siregar, Tongku N. (Buletin Pengabdian, 2021)
The community service activity aims to establish a partnership system with breeders by providing limited goat assistance for six months or one reproductive cycle with the introduction of artificial insemination and ovulation manipulation technology, thus the strengthening of business capital can be increased. This activity involved ten target audiences from Ajee Rayeuk Village, Ingin Jaya Sub-District, Aceh Besar District. Criteria for the target audience were 1) having the lowest income, 2) having experience in raising goats whether their own goats or other people goats, 3) having a pen for at least 4 livestock, and, 4) having family members who are able and have time to focus on managing and caring for their livestock. The community service team was procuring goats based on the criteria that the goat have given birth, clinically healthy, and 3 years old, so the goats had a high productivity performance. The total number of goats provided was 30 goats, with three goats for each target audience. The goats were then subjected to ovulation manipulation technology and artificial insemination.